Swimming in the Antarctic scallop Adamussium colbecki: analysis of in situ video recordings - ANSELL A. D.; CATTANEO VIETTI, RICCARDO; CHIANTORE, MARIACHIARA (1998)
Swimming activity of the Antarctic scallop at a temperature of c. - 1.4" C was analysed using in situ video recordings obtained from a remotely operated vehicle (ROV) in Terra Nova Bay, Ross Sea. Data are presented on swimming trajectories, distance travelled and velocity during a swimming bout, adduction frequency, shell gape angle, and the angular opening and closing velocities of shell. This scallop is an effective swimmer although swimming bouts in response to the ROV were generally short, consisting of 2-5 adduction cycles in the take-off phase followed by 1-4 (exceptionally 14) adductions during level swimming. The maximum velocity during each adduction cycle ranged from 19.443.1 cm s-' and the mean velocity during a swimming bout from 12.0-23.5 cm s-I. Each adduction cycle consists of opening, closing and glide phases of approximately equal duration. Adduction frequency during swimming averaged 1.5 adductions s-I .